Collaborative environment and technologies for building knowledge work teams in network enterprises. (2nd January 2007) - Lee, W.B.; Cheung, C.F.; Tsui, E.; Kwok, S.K.
Efficient sharing of knowledge is crucial in the building of knowledge work team. The importance in developing appropriate collaborative technologies to be embedded in the knowledge generation and sharing processes has been often undermined for the successful launching of Knowledge Management (KM) programmes. This paper outlines the essentials of the new knowledge environment and collaborative technologies that are used to support knowledge work. The type of collaborative technologies and environment required depends on the nature of the business. Two case examples of pending KM programmes, one in an airline industry and another in an electronics manufacturer are illustrated. It is found that a detailed understanding of the business process and customisation and alignment of the technologies are the two most important factors in designing the most appropriate knowledge environment.